Experimental and Analytical Studies of Blade Angle Influences Under Normal and Faulty Conditions - Shawqran A.M.; El-Marhomy A.; Attia M.A.; Abdelaziz A.Y.; Vardhan A.S.S.; Vardhan A.S.S.; Saxena R.K.; Saket R.K. (My University, 2025)
A new blade angle adaptive PI controller is presented in this paper to enhance the wind energy conversion system during normal and faulty conditions. Experimental and analytical work have been carried out to investigate the blade angle influences. Also, validation of the new controller through comparison with conventional PID controller is obtained. The comparison shows that proposed controller achieves acceptable fault ride through operation also the controller is robust even with wind speed variation. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.